PEMBERDAYAAN KADER DESA KERTAMUKTI KABUPATEN BANDUNG BARAT MELALUI KETERAMPILAN KOMUNIKASI - Taufik, Cevi Mochamad; Ghassani, Rizqi; Lusiawati, Ira; Suhaeri; Fitriawati, Diny; Suminar, Erna; Sabarudin, Didin; Aditya, Krisna; Tugiyono, Jentot (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
The welfare of the village community is built through the communication skills of village empowerment cadres (KPMD). As informal officers recruited from community potential, the cadres work as catalysts connecting the village government with village residents. The relationship between cadres and villagers is mainly related to the delivery and implementation of various programs aimed at all villagers. With these roles and duties, the cadres have a very strategic position. Its existence is a driving force that encourages and awakens villagers to participate in the implementation of village community development programs. Given the importance of the role and position of village cadres, lecturers of Communication Studies at the National University of Indonesia (UKRI) conduct community service which aims to provide communication skills to Kertamulya village cadres, Padalarang District, West Bandung Regency, so that all government programs can be understood and conveyed to all villagers. With the lecture and discussion method, it is possible to identify and solve various problems that arise with regard to the communication of cadres. The PkM results show that the cadres gain applied knowledge that can be used in carrying out all the tasks assigned.